Sumbang Caliak dalam Adat Minangkabau: Manifestasi Nilai-Nilai Hadis tentang Etika Pandangan dan Kesopanan Sosial - Rafika Rahmat; Zikri Darussamin (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2025)
Sumbang caliak is a form of prohibition in Minangkabau custom that regulates visual behavior in the context of male-female interactions in social relations. This study aims to analyze sumbang caliak as a manifestation of hadith values related to the ethics of guarding one's gaze (hifzh al-bashar) and social modesty (haya’). Through a living hadith approach, this study examines how the hadith teachings on lowering the gaze are understood normatively and theologically in the cultural practices of the Minangkabau people. This study is a library research that seeks to construct conceptual and theoretical understanding by placing customary texts and hadith as the main sources.  The results of the study show that sumbang caliak is not merely a rule of etiquette, but a representation of a social mechanism to maintain the marwah (self-esteem) of women and men, control the expression of desire, and prevent behavior that has the potential to cause slander or violations of honor. This tradition serves as an epistemological bridge between Minangkabau customs based on the principle of adat basandi syarak, syarak basandi Kitabullah and the values of hadith that emphasize politeness, moderation of desires, and balance in social relationships. Thus, sumbang caliak is a concrete example of how the principle of hadith is lived, internalized, and institutionalized in the customary structures and daily behavior of the Minang people. This research contributes to the strengthening of Islamic anthropological studies and provides an understanding that local customary practices can serve as a medium for the transmission of sustainable sharia values.